2003
DOI: 10.1002/elan.200390133
|View full text |Cite
|
Sign up to set email alerts
|

The Voltammetric Behavior of Superoxide Dismutase/Catalase Mimics

Abstract: The voltammetric behavior of the superoxide dismutase/catalase mimics [(N,N'-bis(salicylidene)ethylenediamine) Mn(III)]Cl (or salenMn(III) chloride) 1 and [(N,N'-bis(3-methoxysalicylidene)ethylenediamine)Mn(III)]Cl (or 3,3'-methoxysalenMn(III) chloride) 2 in acetonitrile is described. Both compounds show quasi-reversible one-electron reductions to the Mn(II) compound. Electroanalytical techniques are used to follow the reaction between superoxide and 1 and 2 and it is shown that it is the reduced Mn(II) compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…We have recently reported the principal features of the redox chemistry for these compounds and their reactions with dissolved dioxygen and electrogenerated superoxide [47]. Under these same conditions we observed no effect in the presence of saturated EDTA and conclude that no decomplexation occurs.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…We have recently reported the principal features of the redox chemistry for these compounds and their reactions with dissolved dioxygen and electrogenerated superoxide [47]. Under these same conditions we observed no effect in the presence of saturated EDTA and conclude that no decomplexation occurs.…”
Section: Discussionsupporting
confidence: 43%
“…The reason for the differences between the prooxidant activities of the two Mn-salens was not determined though we have demonstrated that the rate of superoxide production by 1 is approximately twice that of 2 [47]. This may relate to the aromatic substitution pattern as semiquinone formation can occur under oxidising conditions in vivo to weaken OÁ Á ÁMn interactions.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The same authors found that besides the antioxidant activity, this metal-reduced form may behave as a pro-oxidant by forming superoxide in the presence of relatively high concentrations of dissolved oxygen (O'Hare et al 2003). Supporting evidence was provided by Vezin et al who successfully synthesized superoxide-generating Mn(II)-salen complexes designed for high DNA cleaving activity (Vezin et al 2002).…”
Section: Introductionmentioning
confidence: 91%